Tinjauan Teologis Berdasarkan Kolose 3:21 dan Efesus 6:4 Terhadap Pola Asuh Otoriter Ayah Sebagai Penyebab Post Traumatic Syndrome Disorder (PTSD) - Endang Trisna Gea; Jimmy Sugiarto; Paulus Kunto Baskoro (Pusat Studi Pentakosta Indonesia, 2026)
Parenting styles are very important for children. Fathers play an important role in raising children. This depends on a father's parenting style. Looking at the background of the situation when Paul wrote Colossians 3:21 and Ephesians 6:4, the customs of leaders at that time influenced fathers in raising their children. The author of this study aims to present a theological review of Colossians 3:21 and Ephesians 6:4 regarding authoritarian parenting by fathers as a cause of post-traumatic stress disorder (PTSD). The purpose of this study is to reveal a theological review of Colossians 3:21 and Ephesians 6:4 regarding authoritarian parenting by fathers as a cause of post-traumatic stress disorder (PTSD). To obtain a theological review of Colossians 3:21 and Ephesians 6:4 regarding authoritarian parenting by fathers as a cause of post-traumatic stress disorder (PTSD), qualitative research using the literature method was used. The objectives of this study are: First, to explain authoritarian parenting in the context of Colossians 3:21 and Ephesians 6:4. Second, to explain the meaning of Post Traumatic Stress Disorder (PTSD). Third, to provide solutions for handling children who experience post-traumatic stress disorder (PTSD). With a focus on hermeneutic study of Ephesians 6:4 and Colossians 3:21 to find the best solution for children experiencing post traumatic syndrome disorder (PTSD).AbstrakPola asuh sangat penting bagi seorang anak. Dan ayah memiliki peran penting dalam mendidik anak. Ini tergantung dari pola asuh seorang ayah. Dengan melihat latar belakang situasi yang terjadi pada saat Paulus menulis surat Kolose 3:21 dan Efesus 6:4, yang mana kebiasaan para pemimpin yang terjadi pada saat itu mempengaruhi para ayah dalam mendidik anaknya. Penulis dalam penelitian ini mau memaparkan tinjauan teologis surat Kolose 3:21 dan Efesus 6:4 terhadap pola asuh otoriter ayah sebagai penyebab post traumatic syndrome disorder (PTSD). Tujuan penelitian ini ialah untuk mengungkapkan tinjauan teologis surat Kolose 3:21 dan Efesus 6:4 terhadap pola asuh otoriter ayah sebagai penyebab post traumatic syndrome disorder (PTSD). Untuk memperoleh tinjauan teologis surat Kolose 3:21 dan Efesus 6:4 terhadap pola asuh otoriter ayah sebagai penyebab post traumatic syndrome disorder (PTSD) dengan menggunakan penelitian kualitatif dengan metode kepustakaan. Tujuan dari penelitian ini adalah Pertama, menjelaskan pola asuh otoriter yang terjadi dalam latar belakang surat Kolose 3:21 dan Efesus 6:4. Kedua, menjelaskan makna Post Traumatic Syndrome Disorder (PTSD). Ketiga, memberikan solusi penanganan anak yang mengalami post traumatic syndrome disorder (PTSD). Dengan fokus pengkajian secara hermenetik dari Efesus 6:4 dan Kolose 3:21 untuk menemukan solusi yang terbaik bagi anak yang mengalami post traumatic syndrome disorder (PTSD).